Treatment of Knee Osteoarthritis With Allogeneic Bone Marrow Mesenchymal Stem Cells. Issue 8 (August 2015) - Vega, Aurelio; Martín-Ferrero, Miguel Angel; Del Canto, Francisco; Alberca, Mercedes; García, Veronica; Munar, Anna; Orozco, Lluis; Soler, Robert; Fuertes, Juan Jose; Huguet, Marina; Sánchez, Ana; García-Sancho, Javier
<x xml:space="preserve">Abstract</x> Background Osteoarthritis is the most prevalent joint disease and a common cause of joint pain, functional loss, and disability. Conventional treatments demonstrate only modest clinical benefits without lesion reversal. Autologous mesenchymal stromal cell (MSC) treatments have shown feasibility, safety, and strong indications for clinical efficacy. We performed a randomized, active control trial to assess the feasibility and safety of treating osteoarthritis with allogeneic MSCs, and we obtain information regarding the efficacy of this treatment. Methods We randomized 30 patients with chronic knee pain unresponsive to conservative treatments and showing radiological evidence of osteoarthritis into 2 groups of 15 patients. The test group was treated with allogeneic bone marrow MSCs by intra-articular injection of 40 × 106 cells. The control group received intra-articular hyaluronic acid (60 mg, single dose). Clinical outcomes were followed for 1 year and included evaluations of pain, disability, and quality of life. Articular cartilage quality was assessed by quantitative magnetic resonance imaging T2 mapping. Results Feasibility and safety were confirmed and indications of clinical efficacy were identified. The MSC-treated patients displayed significant improvement in algofunctional indices versus the active controls treated with hyaluronic acid. Quantification of cartilage quality by T2 relaxation measurements showed a significant decrease in poor cartilage areas, with cartilage quality improvements in MSC-treated patients. Conclusions Allogeneic MSC therapy may be a valid alternative for the treatment of chronic knee osteoarthritis that is more logistically convenient than autologous MSC treatment. The intervention is simple, does not require surgery, provides pain relief, and significantly improves cartilage quality.